Relationship between family functioning and sexual identity of adolescent students from educational institutions in Lima - Ramírez Arredondo, Estela (2020)
Objective: to determine the relationship between the variable of family functioning and sexual identityin adolescent students from educational institutions in Lima. Methodology: non-experimental design,quantitative, cross-sectional and correlational type approach. For the measurement of the familyfunctioning variable, the Family Assessment Device (FAD) scale prepared by Epstein et al (1983)was used; and the sexual identity exploration questionnaire (CEIS), prepared by León, Chaigneau,Rodríguez and Peña (2014) was used to measure the sexual identity variable. The sample wasmade up of 285 students in the third, fourth and fifth years of secondary school. Results: A negativerelationship was found between the level of family functioning and the fantasy / homosexual behaviordimension (rho = -.003; p> .05). Likewise, no highly significant relationship was found between familyfunctioning and the dimension according to their sex (rho = -.072; p <.01). However, a highly significantpositive relationship was found with the heterosexual fantasy / behavior dimension (rho = .177; p> .01),that is, the greater the family functioning, the greater the heterosexual fantasy / behavior. Conclusion:There is an negative relationship between family functioning and the homosexual behavior dimensionand a positive relationship between family functioning and the heterosexual behavior dimension.